2020
DOI: 10.1186/s12920-020-00808-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker discovery in attention deficit hyperactivity disorder: RNA sequencing of whole blood in discordant twin and case-controlled cohorts

Abstract: Background A variety of DNA-based methods have been applied to identify genetic markers of attention deficit hyperactivity disorder (ADHD), but the connection to RNA-based gene expression has not been fully exploited. Methods Using well defined cohorts of discordant, monozygotic twins from the Michigan State University Twin Registry, and case-controlled ADHD cases in adolescents, the present studies utilized advanced single molecule … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Other studies suggested that polymorphic loci in RGS2 seem to predict the severity of schizophrenia symptoms (Campbell et al, 2008 ), or they can be associated with the risk of extrapyramidal symptoms induced by typical neuroleptics-haloperidol (Gareeva et al, 2013 ). Recently, RGS2 has also been associated with attention deficit hyperactivity disorder (ADHD; McCaffrey et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested that polymorphic loci in RGS2 seem to predict the severity of schizophrenia symptoms (Campbell et al, 2008 ), or they can be associated with the risk of extrapyramidal symptoms induced by typical neuroleptics-haloperidol (Gareeva et al, 2013 ). Recently, RGS2 has also been associated with attention deficit hyperactivity disorder (ADHD; McCaffrey et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the present ADHD study-case, RNAseq records from the entry GSE159104 ( 43 ) were selected, where two cohorts of patients were already identified and labeled as control (healthy) and ADHD (case-disease). The variability within the genes or proteins involved in the ADHD molecular definition (see Supplementary Methods in Supplementary Material 1 ; Supplementary Tables A, B in Supplementary Material 2 ) was evaluated for the 154 samples (78 control, 76 ADHD) included in the GEO experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-sense transcript to the HLA- DQB1 locus on chromosome 6 is elevated roughly twofold in people with ADHD 174 …”
Section: Plausible Explanation Models For Orx-s Dysfunction Pathways ...mentioning
confidence: 99%